Pedagogic Competency Analysis of Teachers in Indonesia - Damayanti, Rina; Ahmad, Syarwani; Wahidy, Achmad (Yayasan Sembilan Pemuda Indonesia, 2020)
This research was conducted through a qualitative approach. The method used in this research is descriptive method. The instruments used were observation sheets, interview guides, audio and video recording devices and teacher administrative documents. For data testing, data triangulation techniques are used. Furthermore, the data were analyzed using the following steps data collection; data reduction; data display, and verification and conclusion. The results showed that 1) the pedagogical competence of the teacher in managing the learning process at SMP Negeri 1 Prabumulih was classified as good; 2) the obstacles faced by teachers in managing the learning process are teachers' lack of understanding of the 2013 curriculum; scoring system; teachers only rely on textbooks or teacher handbooks in delivering learning materials without trying to find other relevant learning sources; lack of use of learning media; and teachers' inadequate ICT skills; 3) there has been no real effort made by the majority of teachers in overcoming obstacles faced in the management of the learning process.